Telaah Islamic Studies atas Tradisi Pelet Bettheng Masyarakat Desa Pajudan Daleman dan Rombasan Sumenep Madura - Zaitur Rahem (Akademika: Jurnal Keagamaan dan Pendidikan, 2017)
Strong building a community is cultural. Humans can not be separated from the culture created. Every generation has its cultural achievements of each. The cultural movement gradually transformed mindset, character and ideology. Lumbung culture itself has been represented by rural areas. The village with all the trappings of his life, was able to survive and meruwat kebudyaannya, despite continued menggempurnya times with a number of technological progress and civilization. Derap culture in rural areas also ignited masarakat confidence in Indonesia to build a distinctive civilization nusantaranya. All local wisdom in the area of   the archipelago is an insight into life. One of the cultural appearance of the wise is in the village of pellets bettheng Pajudan Daleman and Village Rombasan. These two villages representing the portrait of a civilized life in the island of Madura.[Bangunan kuat suatu komunitas adalah kebudayaan.Manusia tak bisa lepas dari kebudayaan yang diciptakan.Setiap generasi memiliki prestasi kebudayaan masing-masing.Pergerakan kebudayaan tersebut lambat laun menjelma mindset, karakter, dan ideologi.Lumbung kebudayaan sendiri selama ini terwakili oleh kawasan pedesaan.Desa dengan segenap ornamen kehidupannya, masih mampu bertahan dan meruwat kebudyaannya, meski zaman terus menggempurnya dengan sejumlah kemajuan dan peradaban tekhnologi. Derap kebudayaan di kawasan pedesaan juga memantik rasa percaya diri masarakat di Indonesia untuk membangun peradaban khas nusantaranya. Semua kearifan budaya lokal di kawasan nusantara adalah wawasan kehidupan.Salah satu perwajahan kebudayaan arif itu adalah pelet bettheng di desa Pajudan Daleman dan Desa Rombasan.Dua desa ini mewakili potret kehidupan beradab di kawasan pulau Madura.]